Socioeconomic backgrounds and the relationship with food consumption patterns and food adequacy level among low-income consumers in Lahad Datu, Sabah, Malaysia - Zainal Badari, Shamsul Azahari; Selamat, Shafidah (Human Resources Management Academic Research Society (HRMARS), 2024)
The primary objective of this study was to examine the socioeconomic backgrounds of lowincome consumers in Lahad Datu, Sabah, Malaysia, and their association with food consumption patterns and food adequacy levels. A total of 160 respondents were selected through purposive sampling. Food consumption patterns were assessed using the Food Variety Score (FVS), while food adequacy levels were measured using the Malaysian Food Variety Indicator (MFVI). The findings revealed that 47.5% of the respondents had a lower FVS. Cereals and cereal products had the highest mean intake (29.38), followed by vegetables (21.0), while meat had the lowest mean intake (0.0). Similarly, analysis of the MFVI scores demonstrated mean scores of 22.19 for cereals and cereal products, 21.06 for vegetables, and 0.0 for meat. There was a significant relationship between the socioeconomic background, food consumption patterns, and food adequacy levels, particularly concerning the age of the respondents (r=0.254, p=0.010), household size of the respondents (r=0.203, p=0.010), and food consumption patterns (r=0.992, p=0.000). In conclusion, the study found that the food adequacy levels of the respondents were influenced by their age, household size, and food consumption patterns.